Intracranial ependymoma: A retrospective analysis of clinical features, treatment modalities, and long‐term outcome - Amr Badary; Sarah Zuhair Kurdi; Yasser F. Almealawy; Sura N. Alrubaye; Vivek Sanker; Bipin Chaurasia; Oday Atallah (Aging Medicine)
Abstract Objective Ependymomas, rare neuroglial tumors originating from ependymal cells, can occur in the CNS and typically affect the brain's ventricles or spinal cord. Prognosis is influenced by tumor grade, location, resection extent, and preoperative Karnofsky Performance Status Scale (KPSS) scores. This study evaluates clinical features, treatment outcomes, and factors affecting prognosis in patients with intracranial ependymomas. Methods A retrospective review of 23 patients with intracranial ependymomas, treated from 2018 to 2023, was conducted. Data included demographics, clinical presentations, KPSS scores, imaging findings, and treatment details. Outcomes assessed were postoperative complications, recurrence rates, and functional status. Statistical analysis used SPSS version 26, with significance set at p < 0.05. Results The cohort was predominantly male (87.0%), with a mean age of 27 years. Tumors were mostly in the fourth ventricle (82.6%), with an average diameter of 68.9 mm. Complete resection was achieved in 87.0% of cases. Postoperative radiotherapy was given to 91.0% of grade 2 and all grade 3 tumors. Recurrence occurred in 17.4% of grade 2 ependymomas, but none of grade 3. The seven‐month mortality rate was 4.3%. Higher preoperative KPSS scores correlated with better outcomes. Conclusion Complete tumor resection and postoperative radiotherapy are crucial for improved outcomes in ependymomas. Higher preoperative KPSS scores and tumor location significantly impact prognosis. Tumors in the lateral ventricles are associated with higher recurrence risks. These findings highlight the need for aggressive surgical management and personalized adjuvant therapy to enhance patient outcomes.